Effective Practices in School Transitions for Autistic Children and Young People: A Literature Review and Case Study - Campbell, Carole; Daly, Clare; Boyle, James (International Journal of Educational and Life Transitions, 2024)
Supporting children and young people’s school transitions has been a key policy driver for Scottish schools. School transitions can be challenging for children and young people (Hopwood et al., 2016) particularly those on the autistic spectrum (Yazici & Akman, 2020). It is important that schools provide effective transitions practices to maximise the opportunities for students to experience positive school transitions. School transitions in this paper refer to both early years centres to primary school and primary to secondary school. This paper is made up of two related studies. Study One considers the peer-reviewed published literature from 2002–2022, with fifty-five papers meeting the inclusion criteria, to investigate the nature of effective school transitions for autistic children and young people. Included papers were analysed thematically and 13 evidence-based effective practices (EPs) identified. In Study Two these EPs were used as a priori themes to help understand the processes underpinning practice in one Scottish local authority (LA). Results from a semi-stratified sample of 7 transitions policies from the LA revealed that student-centred planning, collaborative working, discussions around additional support needs (ASN) and effective planning were the most noted transitions supports. Staff knowledge of transitions, adaptations for Covid and environmental supports were the least mentioned. Understanding the nature of EPs in this area may facilitate their implementation and help practitioners better support transitions between schools for autistic children and young people.
Keywords: ASD School transitions; school transitions policy; effective practices